1995
DOI: 10.1002/aja.1002030411
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic expression of tenascin‐X suggests a role in limb, muscle, and heart development

Abstract: Tenascin-X (TN-X) is the newest member of the tenascin family of extracellular matrix proteins and it is highly expressed in muscular tissues during development. To gain insight into the possible functions of TN-X during development, we evaluated its expression in the rat embryo. Using an 800 bp cDNA encoding the fibrinogen-like domain of TN-X, we show that TN-X expression begins in migrating cells of the epicardium in the El2 heart. The epicardium provides progenitors of fibrous and vascular tissue to the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 56 publications
5
74
0
Order By: Relevance
“…In developing rats, tenascin-X is expressed in tendon sheaths, ligaments, synovium, muscle, epicardium, and blood vessel adventitia (48), and a similar distribution has also been shown for pigs (49). In mice, tenascin-C and tenascin-X are coexpressed in muscle, gut, skin, and vasculature (50).…”
Section: Tenascin-x Deficiency and Joint Hypermobilitymentioning
confidence: 72%
“…In developing rats, tenascin-X is expressed in tendon sheaths, ligaments, synovium, muscle, epicardium, and blood vessel adventitia (48), and a similar distribution has also been shown for pigs (49). In mice, tenascin-C and tenascin-X are coexpressed in muscle, gut, skin, and vasculature (50).…”
Section: Tenascin-x Deficiency and Joint Hypermobilitymentioning
confidence: 72%
“…This subepicardium is a hydrated ECM, rich in proteins, including collagens I, IV, V, and VI and fibronectin (Tidball, 1992;Hurlé et al, 1994;Ká lmá n et al, 1995;Bouchey et al, 1996;Kim et al, 1999), flectin (Tsuda et al, 1998), fibulin-2 (Tsuda et al, 2001), GP68 (Morita et al, 1998), laminin and proteoglycans (Ká lmá n et al, 1995), vitronectin, fibrillin-2, elastin (Bouchey et al, 1996), and tenascin-X (Burch et al, 1995). It has been shown that both the epicardium and myocardium contribute proteins to this matrix (Bouchey et al, 1996).…”
Section: The Subepicardial Extracellular Environmentmentioning
confidence: 99%
“…Like tenascin-C and tenascin-R, tenascin-X is weakly active as a cell adhesion protein and cells in general do not spread on a tenascin-X substrate [11]. Its major site of expression is in the connective tissue of heart and skeletal muscle as well as in the dermis of skin [12,13]. In the chicken the closest homologue of tenascin-X is tenascin-Y, and judging from its sequence similarity as well as its analogous expression pattern it can be considered as the avian orthologue of tenascin-X [14,15].…”
Section: Introduction: the Tenascin Family Of Extracellular Matrix Prmentioning
confidence: 99%